A pilot study of neonatologists' decision-making roles in delivery room resuscitation counseling for periviable births. Issue 3 (2nd July 2016) - Tucker Edmonds, Brownsyne; McKenzie, Fatima; Panoch, Janet E.; White, Douglas B.; Barnato, Amber E.
ABSTRACT: Background : Relatively little is known about neonatologists' roles in helping families navigate the difficult decision to attempt or withhold resuscitation for a neonate delivering at the threshold of viability. Therefore, we aimed to describe the "decision-making role" of neonatologists in simulated periviable counseling sessions.Methods : We conducted a qualitative content analysis of audio-recorded simulation encounters and postencounter debriefing interviews collected as part of a single-center simulation study of neonatologists' resuscitation counseling practices in the face of ruptured membranes at 23 weeks gestation. We trained standardized patients to request a recommendation if the physician presented multiple treatment options. We coded each encounter for communication behaviors, applying an adapted, previously developed coding scheme to classify physicians into four decision-making roles (informative, facilitative, collaborative, or directive). We also coded postsimulation debriefing interviews for responses to the open-ended prompt: "During this encounter, what did you feel was your role in the management decision-making process?"Results : Fifteen neonatologists (33% of the division) participated in the study; audio-recorded debriefing interviews were available for 13. We observed 9 (60%) take an informative role, providing medical information only; 2 (13%) take a facilitative role, additionally eliciting the patient's values; 3 (20%) take a collaborative role, additionally engaging the patient in deliberation and providing a recommendation; and 1 (7%) take a directive role, making a treatment decision independent of the patient. Almost all (10/13, 77%) of the neonatologists described their intended role as informative.Conclusions : Neonatologists did not routinely elicit preferences, engage in deliberation, or provide treatment recommendations—even in response to requests for recommendations. These findings suggest there may be a gap between policy recommendations calling for shared decision making and actual clinical practice.